2020
DOI: 10.1049/hve2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behaviours of bio‐derived epoxy resins from cashew nutshell liquid

Abstract: In this study, four commercially available bio‐derived epoxy systems (extracted from cashew nutshell liquid) were prepared and characterised. The glass transition temperature (T g), dielectric spectroscopy, DC conductivity and breakdown properties of these epoxy resins were studied. Differential scanning calorimetry (DSC) demonstrated that the T g of the investigated systems ranged from 67 to 122°C. The DC conductivity was very low (<10−16 S cm−1) and comparable to the conventional dielectrics at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…On the second run the event detected is an endothermic second-order transition characteristic of the glass transition of epoxy. The T g of pristine epoxy 92 °C , agrees with the value reported by Mu et al [45]. This value is of 93 °C and 92 °C for bamboo fibres/epoxy composites and bamboo strips/epoxy respectively.…”
Section: Thermal Transitions Of Bamboo/epoxy Compositessupporting
confidence: 90%
“…On the second run the event detected is an endothermic second-order transition characteristic of the glass transition of epoxy. The T g of pristine epoxy 92 °C , agrees with the value reported by Mu et al [45]. This value is of 93 °C and 92 °C for bamboo fibres/epoxy composites and bamboo strips/epoxy respectively.…”
Section: Thermal Transitions Of Bamboo/epoxy Compositessupporting
confidence: 90%
“…CNSO is composed primarily of the chemical molecules anacardic acid, cardanol, cardol, and 2-methylcardol. Natural CNSO, also known as nCNSO, is obtained by distillation at low temperatures, whereas technical CNSO, also known as tCNSO, is obtained by distillation at high temperatures (Mu & Vaughan, 2020). Anacardic acid accounts for 70% of nCNSO, whereas cardol accounts for 18%, cardanol accounts for 5%, and the remaining 30% is made up of a variety of phenols and less polar chemicals.…”
Section: Chemical Structure Of Cnsomentioning
confidence: 99%
“…The Formulite TM series of bio-based epoxies is one such bio-based polymer that several researchers have explored in recent times for its applicability in various engineering sectors. It is derived from natural phenolic materials that are obtained by distilling Cashew nutshell liquids (CNSL) [30][31][32][33][34]. The mechanical strength and water absorption tests conducted on the Formulite TM bio-based epoxy variants showed that they-and particularly the one comprising a combination of Formulite TM 2501A + Formulite TM 2401B-proved to exhibit properties nearing the traditionally used LY556/HY951 synthetic epoxies [35].…”
Section: Introductionmentioning
confidence: 99%